Effect of Gegen Qinlian Decoction on Cardiac Gene Expression in Diabetic Mice - Jing Han; Zhenglin Wang; Wei Xing; Yueying Yuan; Yi Zhang; Tiantian Lv; Hongliang Wang; Yonggang Liu; Yan Wu (International Journal of Genomics)
The aim of this research is to investigate the therapeutic effect of GGQL decoction on cardiac dysfunction and elucidate the pharmacological mechanisms. db/db mice were divided into DB group or GGQL group, and WT mice were used as control. All mice were accessed by echocardiography. And the total RNA of LV tissue samples was sequenced, then differential expression genes were analyzed. The RNA-seq results were validated by the results of RT-qPCR of 4 genes identified as differentially expressed. The content of pyruvate and ceramide in myocardial tissue was also measured. The results showed that GGQL decoction could significantly improve the diastolic dysfunction, increase the content of pyruvate, and had the trend to reduce the ceramide content. The results of RNA-seq showed that 2958 genes were differentially expressed when comparing the DB group with the WT group. Among them, compared with the DB group, 26 genes were differentially regulated in the GGQL group. The expression results of 4 genes were consistent with the RNA-seq results. Our study reveals that GGQL decoction has a therapeutic effect on diastolic dysfunction of the left ventricular and the effect may be related to its role in promoting myocardial glycolysis and decreasing the content of ceramide.